Effects of chemical solvents on coal pore structural and fractal characteristics: An experimental investigation. (1st November 2022) - Zheng, Chunshan; Liu, Shuaili; Xue, Sheng; Jiang, Bingyou; Chen, Zhongwei
Highlights: Pore structural characteristics affected by chemical solvents are experimentally studied. Changes in fractal dimensions of pore surface and pore structure are calculated based on FHH model. Isothermal adsorption-desorption curves of solvent-treated coal show hysteresis phenomenon. Relationship between pore volume, average diameter, SSA and fractal dimensions are established. Results could provide theoretical references for chemical solvents effects on pore properties. Abstract: Chemical solvent treatment is one of the most effective means to improve pore structure of low-permeability coal and increase production of coalbed methane. Low-temperature liquid nitrogen adsorption method, X-ray diffraction (XRD) mineral analysis and fractal theory were adopted to study variations in coal pore structural parameters and fractal characteristics affected by hydrochloric acid (HCl), tetrahydrofuran (THF) and carbon disulfide (CS2 ). Liquid nitrogen adsorption results of coal samples were analyzed using density functional theory (DFT), Brunauer-Emmett-Teller (BET) equation and Barrett-Johner-Halenda (BJH) model. Meanwhile, changes in fractal dimensions of pore surface (D1 ) and pore structure (D2 ) were calculated based on Frenkel-Halsey-Hill (FHH) model. Relationship between pore volume, average pore diameter, specific surface area and two fractal dimensions were established. Results show that: (1) Hysteresis lines exist in all isothermal adsorption-desorption processes of coal. Pores of raw coal are mainly semi-open pores with poor connectivity. The types of pores do not change significantly after THF and CS2 treatment, while the number of pores rise. In contrast, affected by HCl treatment, ink-bottle pores and open pores increase and pore fracture network connectivity becomes better. (2) Pore sizes of treated coal mainly distribute in range of 0–10 nm. After HCl treatment, many closed pores are opened, with growth in proportion of micropores. Meanwhile, specific surface area (SSA) of pores increases by 55.21% and 31.36%, respectively. THF extraction results in an increase in pore volume and SSA. After CS2 extraction, dissolution of organic material increases pore size and further improve volume of transition pores and mesopores. (3) HCl treatment causes decrease in D1 value of pores. However, in organic-solvent-treatment cases, solvent residues retain on coal pores, resulting in growth in D1 value and pore surface becoming rougher. Proportion of total pore volume of transition pores and mesopores of acidized coal decreases and D2 value rises. Pore distribution is more uneven. Relevant results could provide theoretical references for revealing mechanism of chemical solvents effects on gas flow in coal.